2022
DOI: 10.1007/s00134-022-06811-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of vancomycin plus piperacillin–tazobactam with early changes in creatinine versus cystatin C in critically ill adults: a prospective cohort study

Abstract: Purpose: Although dozens of studies have associated vancomycin + piperacillin-tazobactam with increased acute kidney injury (AKI) risk, it is unclear whether the association represents true injury or a pseudotoxicity characterized by isolated effects on creatinine secretion. We tested this hypothesis by contrasting changes in creatinine concentration after antibiotic initiation with changes in cystatin C concentration, a kidney biomarker unaffected by tubular secretion. Methods:We included patients enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 49 publications
2
30
0
1
Order By: Relevance
“…Despite epidemiological data showing an association of AKI with beta-lactam administration, direct causality can be found only rarely. A possible increase in AKI related to the combination of antibiotics, for example, the most frequently used piperacillin and vancomycin, is not based on evidence of causality [ 86 ]. Surprisingly, data suggesting the protective role of a combination of piperacillin and vancomycin exist [ 87 , 88 ].…”
Section: Beta-lactam Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite epidemiological data showing an association of AKI with beta-lactam administration, direct causality can be found only rarely. A possible increase in AKI related to the combination of antibiotics, for example, the most frequently used piperacillin and vancomycin, is not based on evidence of causality [ 86 ]. Surprisingly, data suggesting the protective role of a combination of piperacillin and vancomycin exist [ 87 , 88 ].…”
Section: Beta-lactam Toxicitymentioning
confidence: 99%
“…They bind with higher affinity to renal transporters mediating creatinine secretion and, consequently, serum creatinine levels increase. Thus, the association with AKI defined by creatinine levels should be called pseudotoxicity, rather than defined as a real toxic effect [ 86 ]. As already mentioned, using a single creatinine level in estimating GFR in a critically ill patient is not appropriate, and other approaches, such as measuring cystatin levels or four-hour creatinine clearance, should be prioritized [ 90 , 91 ].…”
Section: Beta-lactam Toxicitymentioning
confidence: 99%
“…Notably, in animal models, piperacillin has been shown to impair tubular secretion of creatinine without causing tubular damage ( Pais et al, 2020 ). A recent prospective study in adults has shown that use piperacillin-tazobactam over cefepime is associated with higher rates AKI as defined by changes in serum creatinine but without concurrent changes in blood urea nitrogen or cystatin C ( Miano et al, 2022 ). Therefore, ideally these pediatric studies would include non-creatinine markers of kidney function such as cystatin C and kidney injury-specific urinary biomarkers such as neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) to distinguish between pseudo-nephrotoxicity from impaired tubular secretion of creatinine and true kidney injury.…”
Section: Who Might Benefit From β-Lactam Precision Dosing?mentioning
confidence: 99%
“…4 The mechanism of AKI in patients on VPT therapy is not well understood; proposed mechanisms include acute interstitial nephritis (AIN), acute tubular necrosis (ATN), pseudo-nephrotoxicity, and intratubular crystal obstruction. 1,5…”
Section: Introductionmentioning
confidence: 99%